PENERAPAN FUNGSI MANAJEMEN DALAM ZAKAT DI YAYASAN PEMBERDAYAAN INSAN MANDIRI (YAPIM) CILEDUG - Zahira Fitriana; Ahmad Asrof Fitri; sobirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the implementation of management functions planning, organizing, actuating, and controlling in the management of zakat at Yayasan Pemberdayaan Insan Mandiri (YAPIM) Ciledug. This research employs a qualitative approach with a field research design, emphasizing an in-depth understanding of organizational dynamics in zakat management. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model. The results show that the implementation of management functions at YAPIM has been carried out systematically but has not yet reached optimal effectiveness. The planning function is reflected in structured programs for zakat collection and distribution, though still lacking a data-based approach. The organizing function demonstrates a clear division of labor, yet coordination across divisions remains inconsistent. The actuating function reveals strong moral commitment and community participation but limited managerial competence among amil zakat. The controlling function operates through routine evaluation meetings, though still conducted manually without a digital monitoring system. Overall, YAPIM successfully integrates modern management principles with Islamic values such as amanah (trust), transparency, and justice, creating a model for accountable and faith-based zakat governance. The study recommends enhancing human resource capacity and digital transformation to strengthen efficiency and public trust in zakat institutions. Keywords: Management Functions, Zakat Management, Islamic Management, YAPIM, Accountability